Croconaines as molecular materials for organic electronics: synthesis, solid state structure and use in transistor devices. Issue 15 (17th March 2016) - Punzi, A.; Capozzi, M. A. M.; Fino, V.; Carlucci, C.; Suriano, M.; Mesto, E.; Schingaro, E.; Orgiu, E.; Bonacchi, S.; Leydecker, T.; Samorì, P.; Musio, R.; et al.
Abstract : Indolenine-based croconaines are synthesized, their structure and solid state organization are investigated together with their electronic properties in thin-film transistors. Abstract : A series of indolenine-based croconaines has been synthesized and their molecular structure has been investigated together with their solid state organization. Ambipolar semiconducting properties have been demonstrated in thin-film transistors, suggesting croconaines as a new class of molecular materials for organic electronics.